2003
DOI: 10.1111/j.1745-4530.2003.tb00591.x
|View full text |Cite
|
Sign up to set email alerts
|

DIELECTRIC PROPERTIES of STARCH SOLUTIONS AS INFLUENCED BY TEMPERATURE, CONCENTRATION, FREQUENCY and SALT

Abstract: Dielectric properties of starch solutions (1 to 4% w/w) were evaluated at temperatures ranging from 20 to 80C at 10, 20 and 30 MHz. the effect of added salt (0.2 and 0.5% w/w) was investigated in relation to changes in trends exhibited by the relative permittivity, loss factor and penetration depth. the relative permittivity ranged from 46 to 308 and 65 to 92 for solutions with and without salt, respectively. the corresponding loss factor ranged 266 to 4133 and 9 to 266, respectively. Temperature, frequency, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…Umbach et al (1992) observed that heating caused an increase in e 00 values in various starch solutions. Similar results were obtained by Piyasena et al (2003) for corn starch solutions when the temperature was increased from 20°C to 80°C at a frequency of 10 MHz. In potato, wheat, corn, and waxy corn starch slurries (5-30% w/w) at 2.75 GHz (Ryynänen et al, 1996) and in wheat, tapioca, rice, corn, waxy corn and high-amylose starches at 2.45 GHz (Ndife et al, 1998), it was found that when the starch was already gelatinized, as in the present case, the mobility of water increased with temperature and heating caused a slight increase in the loss factor.…”
Section: Dielectric Propertiessupporting
confidence: 86%
See 2 more Smart Citations
“…Umbach et al (1992) observed that heating caused an increase in e 00 values in various starch solutions. Similar results were obtained by Piyasena et al (2003) for corn starch solutions when the temperature was increased from 20°C to 80°C at a frequency of 10 MHz. In potato, wheat, corn, and waxy corn starch slurries (5-30% w/w) at 2.75 GHz (Ryynänen et al, 1996) and in wheat, tapioca, rice, corn, waxy corn and high-amylose starches at 2.45 GHz (Ndife et al, 1998), it was found that when the starch was already gelatinized, as in the present case, the mobility of water increased with temperature and heating caused a slight increase in the loss factor.…”
Section: Dielectric Propertiessupporting
confidence: 86%
“…This observation was not surprising, since the penetration depth is inversely related to the loss factor; however, other property such as the dielectric constant are also involved in the d calculation. The decrease in d with salt was also observed by Piyasena et al (2003) in corn starch solutions.…”
Section: Dielectric Propertiessupporting
confidence: 61%
See 1 more Smart Citation
“…For RF heating, penetration depth is generally greater than 1 m, and can be determined from a relationship that embodies the dielectric constant, the loss factor, the speed of wave propagation in vacuum, and, operating frequency (Orfeuil, 1987). Depending on concentration and temperature, the penetration depth of starch solutions ranged from 0.2 to 2.1 m in the radio frequency range, while salt enriched starch solutions had comparatively low penetration depths (Piyasena, Ramaswamy, Awuah, & Defelice, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Authors and year Frequency (MHz) Products assessed Temperature range (°C) Wang et al (2003b) 27 and 40 Whey protein gel, macaroni noodles, cheese sauce 15À120 Wang et al (2003a) 1À1800 Fruits 20À52 Piyasena et al (2003b) 10, 20 and 30 Starch solution (1-4%, w/w) 20À80 Zhang et al (2004b) 27.12 Luncheon roll and white pudding meat batter 5À85 Guan et al (2004) 1À1800 Mashed potato 20À120 Al-Holy et al (2005) 27 Salmon (0.8% and 2.3% total salt) 20À80 Lyng et al (2005) 27.12 Ranges of meats and ingredients Room temperature Brunton et al (2006) 27.12 Beef muscle 5À90 Sacilik et al (2006) 0.05À10 Flaxseeds 22 ± 3 Ragni et al (2007) 20À1800 Egg during storage Room temperature Sacilik et al (2007) 0.05-10 Safflower seed Room temperature Farag et al (2008) 27.12 Frozen meat blends À18 to 10 dielectric properties of three different beef meat blends (lean, fat and 50:50 mixture) over a temperature range À18 to +10°C. In the region of thawing (À3 to À1°C), e 0 and e 00 values at 27.12 MHz were significantly higher (P < 0.05) than at other measured temperatures for the three blends.…”
Section: Factors Influencing Dielectric Properties Of Foodsmentioning
confidence: 99%